The Influence of Leadership Style and Environment Work to Work Motivation of SMP Teachers in Bandar Sribhawono Distric Lampung Timur District - Muhammad Ihsan Dacholfany; Emawati Emawati (Universitas Muhammadiyah Enrekang, 2022)
This study aims to investigate: (1) the Influence of leaderships style toward Teachers’ Work Motivation at Junior High Schools in Bandar Sribhawono Distric, East Lampung Regency, (2) the Influence of work environment toward Teachers’ Work Motivation at Junior High Schools in Bandar Sribhawono Distric, East Lampung Regency, and (3) the influence of leaderships style and work environment toward teachers’ work motivation at Junior High Schools in Bandar SribhawonoDistric, East Lampung Regency. This was a quantitative study. The research population comprised teachers at Junior High Schools in Bandar Sribhawono Distric, East Lampung Regency. The sample consisted of 35 respondents from 9 Junior High Schools in Bandar SribhawonoDistric, East Lampung Regency. The research instruments were a questionnaire, observation, and interview. The data analysis technique in the study was multiple regression analysis. The results of the study are as follows. (1) There is a significant and positive influence of leadership style toward teachers’ work motivation. It can be seen from the result of TCount is 1,689 greater that Ttabel is 1,689 and the significant value was 0,000 at the significant level of 5% (0,05). So it can be said that 0,000<0,05. The influence value of leadership style toward teachers’ work motivation is 43.2%. (2)There is a significant and positive influence of work environment toward teachers’ work motivation. It can be seen from the result of TCount is 7,812 greater that Ttabel is 1,689 and the significant value was 0,000 at the significant level of 5% (0,05). So it can be said that 0,000<0,05. The influence value of work environment toward teachers’ work motivation is 39,0%. (3) There is a significant and positive influence of leadership style and work environment toward teachers’ work motivation. It can be seen from the result of FCount is 31,112 greater that Ttabel is 2,247 and the significant value was 0,000 at the significant level of 5% (0,05). So it can be said that 0,000<0,05. The influence value of leadership style and work environment toward teachers’ work motivation is 66,0%.